Contribution of Earthworms to Increase Soil Fertility and Soil Organism Activities - KOSMAN, EA; GITOSUWONDO, SUBOWO (Indonesian Center for Agriculture Land Resource Development, 2010)
Upland in the wet tropical region is dominated by acid soils, low organic matter content, and compacted subsoil layer (especially argillic horizone). The compacted soil inhibit penetration of plant roots and surface water infiltration and increase surface runoff and soil erosion, and low soil productivity. Soil fertility restoration through mechanical processing is difficult to be done, beside damaging the plant roots but also increasing soil erosion. Empowerment of earthworms in their life cycle can make a hole in the soil (burrower), prevent soil compaction, improve soil aeration, spreading organic matter and organic matter inhibits the rate of depreciation of land, and increase soil biological activity, and further can improve soil fertility without disrupting growth plants.